PROSES AFIKSASI CRIKAK “DUDU RAMA LAN SHINTA” KARYA SURYADI WS. SEBAGAI PEMAHAMAN MAKNA KATA BERBAHASA JAWA - Asri, Ella Purwita; Addila, Jasmine Findy; Aprillia, Jenny (Universitas Sebelas Maret, 2025)
THE AFFIXATION PROCESS IN CRIKAK 'DUDU RAMA LAN SHINTA' BY SURYADI WS. AS AN UNDERSTANDING OF JAVANESE WORD MEANINGSStudying affixations has become a common thing for literature enthusiasts. This research examines affixations in the crikak text entitled